A Lexical-Semantic Study of Terms Related to Agricultural Technology in Uzbek and English Languages - Rasulova, Gulmira (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. This study conducts a thorough Lexical-Semantic analysis of terms related to agricultural technology in both Uzbek and English languages. Utilizing a comparative approach, the research explores linguistic nuances, cultural influences, and semantic variations in the lexicons of these languages within the context of agricultural technology. By examining specialized texts and employing semantic analysis tools, the study aims to unravel the intricate interplay between language, culture, and technological concepts. Methods. The research employed a comparative analysis approach, utilizing a corpus of agricultural technology-related texts in both Uzbek and English. Specialized dictionaries, academic publications, and industry documents were examined to compile a comprehensive list of terms. Semantic analysis tools were then employed to discern the connotations and nuances associated with each term. Results. The Uzbek language, with its Turkic roots, reveals a lexicon deeply intertwined with agricultural practices. Terms often reflect the region's rich agricultural history, emphasizing the significance of crops and farming techniques unique to Uzbekistan. The study identifies linguistic patterns and semantic shifts that distinguish Uzbek agricultural technology discourse. English, as a global lingua franca, showcases a diverse and dynamic lexicon in the realm of agricultural technology. Conclusion. This Lexical-Semantic study provides valuable insights into the terms associated with agricultural technology in Uzbek and English. By unraveling the intricacies of language within this domain, the research contributes to a deeper understanding of how linguistic choices influence perceptions and communication in the field of agricultural technology.